Space Walk

David is an astronaut in the International Space Station. A part of a satellite that is 310 310 m away is broken, and David needs to fix it. He gets there with a jetpack which can be used to either accelerate or decelerate with 0.8 m/s 2 0.8 \text{ m/s}^2 .

David starts at rest. He then starts accelerating with his jetpack, in the direction of the satellite. After some time, he stops accelerating and immediately starts decelerating, until he gets to the satellite, which he reaches with a velocity of 4 m/s 4 \text{ m/s} .

How long in seconds does it take David to reach the satellite?

Thanks to Sreejato Bhattacharya for the image!


The answer is 35.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Discussions for this problem are now closed

Tim Vermeulen
Jan 29, 2014

Say, David accelerates for x x seconds. After this acceleration, his velocity is 0.8 x m/s 0.8x \text{ m/s} and the distance he covers while accelerating is s 1 = 0.4 x 2 m s_1 = 0.4x^2 \text{ m} . After that, David decelerates for 0.8 x 4 0.8 \dfrac{0.8x-4}{0.8} seconds, with an average velocity of 0.8 x + 4 2 m/s \dfrac{0.8x+4}{2} \text{ m/s} . The distance David covers while decelerating is s 2 = 0.8 x 4 0.8 0.8 x + 4 2 = 0.64 x 2 16 1.6 = 0.4 x 2 10 m . s_2 = \dfrac{0.8x-4}{0.8} \cdot \dfrac{0.8x+4}{2} = \dfrac{0.64x^2 - 16}{1.6} = 0.4x^2 - 10 \text{ m}. Hence, the total distance David travels is s 1 + s 2 = 0.4 x 2 + ( 0.4 x 2 10 ) = 0.8 x 2 10 = 310 m x = 20 seconds . s_1 + s_2 = 0.4x^2 + (0.4x^2 - 10) = 0.8x^2 - 10 = 310 \text{ m} \implies x = 20 \text{ seconds}. David decelerates for 0.8 x 4 0.8 = 15 \dfrac{0.8x-4}{0.8} = 15 seconds, for a total time of 20 + 15 = 35 20 + 15 = \boxed{35} seconds.

If the image doesn't load, go to: http://s17.postimg.org/e60dc2ouz/Untitled<em>3.jpg If the image doesn't load, go to: http://s17.postimg.org/e60dc2ouz/Untitled 3.jpg

Sreejato Bhattacharya - 7 years, 4 months ago

because fixing a satellite is too mainstream :D

Sherif Elmaghraby - 7 years, 4 months ago

"For Brilliant"?

Ahaan Rungta - 7 years, 4 months ago

If the image doesn't load, go to: https://i.imgur.com/X3CusD5.jpg If the image doesn't load, go to: https://i.imgur.com/X3CusD5.jpg

Sreejato Bhattacharya - 7 years, 4 months ago

solving by graph could be simpler ( v-t graph)

Anirudha Nayak - 7 years, 4 months ago

Yes, but what's the fun of that?

Tim Vermeulen - 7 years, 4 months ago

can somebody explain in further detail how to work our how long he deaccelerates for and his average velocity at the time?

Khie Biggss - 7 years, 4 months ago

At the start of his deceleration, David has a velocity of 0.8 x m/s 0.8x \text{ m/s} , and at the end his velocity is 4 m/s 4 \text{ m/s} . As his deceleration is constant, his average velocity during the deceleration process is 0.8 x + 4 2 m/s \dfrac{0.8x + 4}{2} \text{ m/s} .

Also, we know that his deceleration causes a loss in velocity of 0.8 x 4 m/s 0.8x - 4 \text{ m/s} , and he decelerates with 0.8 m/s 2 0.8 \text{ m/s}^2 , so he decelerates for 0.8 x 4 0.8 \dfrac{0.8x - 4}{0.8} seconds.

Tim Vermeulen - 7 years, 4 months ago
Clarence Chew
Mar 18, 2014

Say instead of arriving at the satellite, David decelerates to 0 m / s 0 m/s .

The extra time he needs is 4 m / s 0.8 m / s 2 = 5 s \frac{4m/s}{0.8m/s^2}=5s .

The extra distance he travels is 0.8 m / s 2 × ( 5 s ) 2 2 = 10 m \frac{0.8m/s^2 \times (5s)^2}{2}=10m .

Hence his total distance is 310 m + 10 m = 320 m 310m+10m=320m .

Due to symmetry, we can now say he accelerates for 160 m 160m (which is half of 320 m 320m ).

Time spent accelerating = 2 × 160 m 0.8 m / s 2 = 20 s =\sqrt{\frac{2 \times 160m}{0.8m/s^2}}=20s .

He also spent 20 s 20s decelerating (due to symmetry).

There is 5 s 5s extra we added in front.

So, the time David spends = 20 s + 20 s 5 s = 35 s =20s+20s-5s=35s .

Gery Wahyu
Feb 5, 2014

s = s 1 + s 2 s = s_1 + s_2

V t 2 = V 0 2 + 2 a s V^2_t = V^2_0 + 2 \cdot a \cdot s

s = V t 2 V 0 2 2 a s = \frac{V^2_t - V^2_0}{2 \cdot a}

V t V_t of s 1 s_1 = V 0 V_0 of s 2 s_2 let's call it as V V

s 1 = V 2 0 1.6 s_1 = \frac{V^2 - 0}{1.6}

s 2 = V 2 4 2 1.6 s_2 =\frac{V^2 - 4^2}{1.6}

s = s 1 = s 2 s = s_1 = s_2 s = V 2 1.6 + V 2 16 1.6 s=\frac{V^2}{1.6} + \frac{V^2-16}{1.6}

310 = 2 V 2 16 1.6 310 = \frac{2V^2-16}{1.6}

512 = 2 V 2 512 = 2V^2 256 = V 2 256 = V^2

V = 16 V = 16 V = V 0 + a t 1 V=V_0 + a \cdot t_1 16 = 0.8 t 2 16=0.8\cdot t_2

t 1 t_1 = 20 4 = 16 a t 2 4=16-a\cdot t_2

t 2 = 15 t_2=15 t = t 1 + t 2 t=t_1+t_2

t = 35 t=35

Captain Awesome
Feb 15, 2014

In order to solve this problem, I used the Work-Energy Theorem and a few Kinematics equations. We were given with:

a = 0.8 v 1 = 0 v 3 = 4 a = 0.8\\ v_1 = 0\\ v_3 = 4

v 1 v_1 corresponds to his speed at time t 1 t_1 . Similarly, v 3 v_3 corresponds to his speed at time t 3 t_3 . We do not know (yet) what is v 2 v_2 or t 2 t_2 .

For t 1 t_1 to t 2 t_2 , the Work-Energy Theorem states that:

1 2 m v 2 2 1 2 m v 1 1 = m a x \frac{1}{2}mv_2^{2} - \frac{1}{2}mv_1^{1} = ma\cdot{x}

where x x is the displacement he has traveled for the first part of the 310-m trip. Cancelling m m and revising the equation we have:

v 2 2 v 1 2 = 2 a x v_2^{2} - v_1^{2} = 2a\cdot{x}

Now, for the second part of the trip, that is, from t 2 t_2 to t 3 t_3 :

1 2 m v 3 2 1 2 m v 2 2 = m a ( 310 x ) \frac{1}{2}mv_3^{2} - \frac{1}{2}mv_2^{2} = -ma\cdot{(310-x)}

The total work done for this time interval is negative because he has slowed down. Again, cancelling m m and readjusting the equation:

v 3 2 v 2 2 = 2 a ( 310 x ) v_3^{2} - v_2^{2} = -2a\cdot{(310-x)}

Adding equations 2 and 4, we will have:

v 3 2 v 1 2 = 2 a ( 310 2 x ) v_3^{2} - v_1^{2} = -2a\cdot{(310-2x)}

But, since v 1 = 0 v_1 = 0 , we should get:

v 3 2 2 a + 310 = 2 x \cfrac{v_3^{2}}{2a} + 310 = 2x

By substitution, x = 160 x = 160 . Going back to equation 2, we should get v 2 = 16 v_2 = 16 . Now, substituting all the values to the following, and thus getting t 1 t_1 and t 2 t_2 :

a = v 2 v 1 t 1 a = v 3 v 2 t 2 t 1 + t 2 = 35 a = \cfrac{v_2 - v_1}{t_1}\\ -a = \cfrac{v_3 - v_2}{t_2}\\ t_1 + t_2 = \boxed{35}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...